Bad splits in orthognathic surgery, prevention and management - Peltoperä, Samuli (My University, 2025)
A “Bad split” refers to an unfavorable fracture of the mandible or maxilla that occurs during an osteotomy procedure, potentially complicating the surgical outcome. This study aims to identify and discuss the most relevant literature-based methods for management and prevention of bad splits in orthognathic surgery, focusing on bilateral sagittal split osteotomies (BSSO) and Le Fort I osteotomies. Electronic searches were conducted in 2024 across PubMed, Scopus and Web of Science databases resulting in total of 30 studies. Articles on BSSO and Le Fort I were searched individually, with inclusion criteria targeting studies reporting incidence, fracture types, management and outcome. The incidence of bad splits in BSSOs ranged from 0.45% to 11.2%, while in Le Fort I osteotomies it ranged from 0% to 2.4%. Most bad splits can be treated intraoperatively and not all need to be treated. Osteosynthesis was the primary treatment method in all articles, with postoperative intermaxillary fixation (IMF) utilized for more complex fracture. Despite the complicating potential of bad splits, they are typically viewed as complications without long-term consequences. Among the studies reporting patient outcomes related to bad splits during BSSO, 9.1% of patients experienced complications affecting the outcome. A thin mandibular buccal cortex was associated as a potential risk factor for bad splits. The increasing use of 3D planning may reduce the risk for bad splits in the future, as 3D imaging reveal abnormal and demanding variation of the anatomy of both the mandible and maxilla.